On Centrally Regular Modules and Centrally Semiregular Modules - Jabbar, Adil Kadir (Sulaimani Journal for Pure and Applied Sciences, 2009)
In this paper, two new modules are defined, which we call centrally regular and centrally semiregular modules and several properties of them are proved. Also, we have determined so many conditions under which regular (resp. semiregular) modules and centrally regular (resp. centrally semiregular) modules are equivalent.
Keywords: regular modules; semiregular modules; small modules,centrally regularmodules; centrally semiregular modules